Kejahatan terhadap tubuh & nyawa - Chazawi, Adami (Jakarta : Divisi Buku Perguruan Tinggi, RajaGrafindo Persada, 2001)
Violent crimes and murder according to Indonesian Criminal Law
Includes bibliographical references (p. 127-129)
Keywords: Murder -- Indonesia; Violent crimes -- Indonesia